2012
DOI: 10.1111/j.1399-5448.2012.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive deterioration of β-cell function in obese youth with type 2 diabetes

Abstract: Objective In adults, type 2 diabetes (T2DM) is characterized with progressive deterioration in insulin secretion. Data are scanty in youth. We investigated prospectively the change in β-cell function and in insulin sensitivity in youth with T2DM. Research Design and Methods Six adolescents with T2DM [hemoglobin A1c (HbA1c) 6.6 ± 1.0%] underwent evaluation of hepatic glucose production (HGP; [6,6-2H2] glucose), insulin-stimulated glucose disposal (Rd; hyperinsulinemic-euglycemic clamp), first- and second-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 21 publications
6
78
1
1
Order By: Relevance
“…This is consistent with reports of progressive deterioration of beta-cell function over time in youth with T2DM [5, 6]. …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with reports of progressive deterioration of beta-cell function over time in youth with T2DM [5, 6]. …”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, the Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) study demonstrated that most youth with T2D can be safely weaned from insulin early in the course of the disease and achieve target HbA 1c levels while being treated with metformin alone [4]. However, deterioration of beta-cell function seems to be more rapid in youth with T2D than in adults with T2D [5, 6], leading to early loss of metabolic control with metformin monotherapy. For example, glycemic control deteriorated in ∼50% of the TODAY study participants being treated with metformin alone during the 12 months after randomization, requiring additional therapy with insulin [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to point out that the AAP guidelines for the management of T2DM have recently been published and have introduced an important modification in regards to the International Society for Pediatric and Adolescent Diabetes /International Diabetes Federation (ISPAD/IDF) guidelines, that is the recommendation to start immediately a combined pharmacological/behavioral therapy in all patients, avoiding the first non pharmacological step based on lifestyle changes alone, which, in contrast has been recommended by the ISPAD/IDF Consensus for all asymptomatic patients with HbA1c<7 % and blood glucose<130 and 180 mg/dl in fasting and post-prandial conditions respectively [31,37]. This novel recommendation relies on the evidence of poor compliance to lifestyle changes in youth and is reinforced by recent evidence of very rapid deterioration of β-cell function in obese youth after diagnosis of T2DM [37,38]. The "Treatment Options for Type 2 Diabetes in Adolescents and Youth" (TODAY) study, a recent three arms randomized clinical trial involving 699 obese adolescents with T2DM, showed that metformin combined with a lifestyle intervention program is less effective than metformin combined with rosiglitazone in reducing the rate of deterioration of glucose control, suggesting that monotherapy with metformin may not be sufficient to stop the deterioration of β-cell function [39••].…”
Section: Disturbances Of Glucose Homeostasismentioning
confidence: 99%
“…β-cell function in overweight and obese adolescents is impaired relative to insulin sensitivity [66]. This is due to the β-cell function rapidly declining, even without significant changes occurring concurrently, with peripheral or hepatic insulin sensitivity [67]. At the time of diagnosis with T2DM, adolescents already present with β-cell dysfunction that is comparable to that observed in their adult counterparts [68].…”
Section: Pancreatic Complicationsmentioning
confidence: 99%